Effect of the Boron Concentration in Irrigation Water on the Elemental Composition of Edible Parts of Tomato, Green Bean, Potato, and Cabbage Grown on Soils With Different Textures - Rékási, Márk; Ragályi, Péter; Füzy, Anna; Uzinger, Nikolett; Dobosy, Péter; Záray, Gyula; Szűcs-Vásárhelyi, Nóra; Makó, András; Takács, Tünde (Frontiers in Plant Science, 2021)
The most important environmental source of boron (B) contamination is irrigation water. Data on the effect of B on the element composition in the edible parts of vegetables are scarce. A greenhouse pot experiment investigated the effect of irrigation water containing 0.1 and 0.5 mg/L B on the biomass, elemental (B, Mg, K, Fe, Cu and Zn) composition and photosynthetic parameters of tomato (Solanum lycopersicum), green bean (Phaseolus vulgaris), potato (Solanum tuberosum) and cabbage (Brassica oleracea) plants grown in 10 kg sand, silty sand or silty soil. The biomass of the edible part was unaffected by B treatment. The soil type determined the effect of B irrigation on the element composition of vegetables. B content increased by 19 % in tomato grown on silty soil. The 0.1 mg/L B treatment facilitated tomato fruit ripening on all soils and 0.5 mg/L B treatment doubled its chlorophyll content index (CCI) on silty soil. The 0.5 mg/L B treatment negatively affected the nutritional value of green bean on all soils, decreasing the Fe and K contents by an average of 83 and 34 %, respectively. The elemental composition of potato was unaffected by the treatments but CCI of potato leaves increased in the 0.5 mg/L B treatment by 26%. B content increased in cabbage grown on light textured soils, by 39 %. As a conclusion B concentration in irrigation water up to 0.5 mg/L had no significant beneficial or adverse effect on the investigated vegetables but 0.1 mg/L B treatment could shorten tomato fruit maturation time on B-poor soils. The B levels in vegetables remained suitable for human consumption.